A bibliometric and visual analysis of indoor occupation environmental health risks: Development, hotspots and trend directions. (1st June 2021) - Zhang, Jingdong; Jiang, Luping; Liu, Zehua; Li, Yanan; Liu, Kangli; Fang, Ruying; Li, Honghu; Qu, Zhiguang; Liu, Chaoyang; Li, Fei
Abstract: With the advancement of industrialization, the health risks in occupational environments are attracting increasing attention, and growing efforts have been devoted to environmentally friendly production and sustainable development in the manufacturing industry. As an industrial area, the indoor occupational environment was of necessity to be considered when assessing health risks in the workplace. However, no such systematic analysis has been performed and make it difficult to grasp deeper insights into indoor occupational environmental health risks. Therefore, an in-depth bibliometric and visual analysis was conducted using Citespace to analyze the knowledge structure, hot topics, and trend directions of this field based on 1211 publications from the Web of Science Core Collection. The results showed that 235 institutions of 58 countries have published articles in this field. The United States was the most productive contributor, with numerous publications and active institutions. Indoor Air, Environmental Health Perspectives, and Atmospheric Environment were the three most cited journals. Additionally, collaboration between authors tends to occur in groups and becomes frequent in recent years. According to the co-occurrence article and keywords analyses, three hot topics in indoor occupation environmental health risks were recognized, including "indoor air quality", "health risks", and "occupational exposure". Moreover, the keywords burst analysis suggested that the topics of sustainable management and green production topics within the manufacturing industry are emerging trends. Besides, the identification of occupational pollutants and design of research methods will advance. To our best knowledge, this study is the first to specifically visualize the research field of indoor occupation environments, and is conducive for identifying current research hots pots and predicting potential future research directions. Graphical abstract: Image 1 Highlights: Industrial indoor environment may present occupational health risks. Bibliometric analysis regarding the development, hotspots and trends was performed. The United States played a leading role in this research field. Three hot topics were recognized with high frequency and centrality. Energy saving, pollutant identification, research method design are common trends.